Pengaruh Kepemimpinan yang Melayani dan Budaya Sekolah sebagai Upaya Mengurangi Dampak Learning Loss di SMA Negeri 14 Palembang - Yeni Silvienti; Bukman Lian; Muhammad Juliansyah (Journal Of Administration and Educational Management (ALIGNMENT), 2023)
The research aims to determine servant leadership and school culture to reduce the impact of learning loss at SMA Negeri 14 Palembang. This quantitative research explores the influence of service leadership and the culture of excellence in schools in overcoming learning loss. Data was collected from a sample of SMA Negeri 14 Palembang teachers using a questionnaire with triangulation of observations and documentation studies. The results of the research show that there is a 31% influence of servant leadership on learning loss recovery efforts, there is a 10.4% influence of school culture on learning loss recovery efforts, and there is a joint influence between servant leadership and school culture on learning loss recovery efforts at SMA Negeri 14 Palembang it was 48.52%. In conclusion, there is the influence of servant leadership and school culture to reduce the impact of learning loss. Keywords: Learning Loss, Servant Leadership, School Culture